Acanthosis nigricans: relation with type 2 diabetes mellitus, anthropometric variables, and body mass in Indians. Issue 958 (5th August 2005) - Grandhe, N P; Bhansali, A; Dogra, S; Kumar, B
Abstract : Objective: To determine the prevalence of acanthosis nigricans (AN) in type 2 diabetes mellitus (T2DM) and its correlation with various anthropometric measurements in Indians. Methods: One hundred and fifty consecutive subjects with T2DM attending the diabetes clinic at a tertiary referral centre in North India were considered as cases and 150 age and sex matched healthy attendants of non-diabetic subjects as controls. All the cases and controls were screened for the presence of AN and its severity. Anthropometric measurements of all of them were measured in standard method. Regression analysis was done to determine the association of AN with T2DM and various anthropometric measurements. Results: The prevalence of AN in subjects with diabetes and healthy controls was 62.6% and 40% respectively, and this difference was significant (p<0.05). Body mass index (BMI) between cases and controls was comparable by chance. There was a statistically significant correlation of increasing severity of AN with increasing BMI, waist circumference, hip circumference, waist-hip ratio, skinfold thickness, and body fat percentage in diabetic patients. However, in regression analysis after considering all the confounding factors there was a significant correlation of AN, only with diabetes mellitus and BMI. Conclusions: Indians have high prevalence of AN and it is an independent cutaneous marker of both T2DM and BMI.